The Effect Of Audio Visual Media In Improving Students' Writing Skills - Mansyur Rahman; Suryadi Ishak; Nurmayanti Nurmayanti (Journal of Humanities, Social Sciences, and Education, 2025)
This study aims to describe: 1) the use of audio-visual media on the learning process, 2) students' writing skills, 3) the effect of using audio-visual media on students' writing skills. The type of research used is experimental. The population in this study were all fourth grade students UPT SDN Tile-Tile No. 9 Kepulauan Selayar, totaling 54 students. The sample used in this study was 54 people who were divided into the experimental group and the control group. The data obtained were analyzed by normality and homogeneity tests which showed that the research data were normally distributed and homogeneous and continued with hypothesis testing using t-test. The results of the study show: 1) The teacher has carried out learning using audio-visual media very well. Similarly, student activity in the learning process is very good, 2) students' writing skills have increased from the middle category to the high category, 3) there is a significant effect of using audio visual media on writing skills.